2012
DOI: 10.1007/s10965-011-9781-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of chitosan/clay (nano)composites: a silanol quaternary ammonium intercalated clay

Abstract: Chitosan/clay (nano)composites were prepared by using a special quaternary ammonium intercalating agent coupled with a silanol group to facilitate the organic clay formation. Exfoliated clay in the chitosan matrix was attained at the higher intercalant dosages through X-ray diffraction (XRD) and transmission electron microscope (TEM) analyses. Optical transmittance for the (nano)composites increased slightly with increasing the amount of intercalants in the clays. In light of the hydrophobic component on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…The different letters in each column indicate significant differences. C: Chitosan N: Nanoclay agreement with similar study that reported the same results (21). Chitosan affected growth of all tested microorganisms including Gram-positive and Gram-negative bacteria, mold and yeast indicators.…”
Section: Discussionsupporting
confidence: 86%
“…The different letters in each column indicate significant differences. C: Chitosan N: Nanoclay agreement with similar study that reported the same results (21). Chitosan affected growth of all tested microorganisms including Gram-positive and Gram-negative bacteria, mold and yeast indicators.…”
Section: Discussionsupporting
confidence: 86%
“…According to Figure 2 10 to 50 min, as more and more chitosan occupied the active adsorption sites on the bentonite [18]. The increase of chitosan loading became stagnant from 50 to 90 min, with a maximum value of 112.62 mg/g after 50 min of reaction.…”
Section: Chitosan Loading Parametersmentioning
confidence: 93%
“…Recently, the results of researches on organic/inorganic nanocomposites to further improve their performance have been reported. Chiu et al reported the investigation of chitosan/clay nanocomposites that were prepared by using a special quaternary ammonium intercalating agent coupled with a silanol group to facilitate the organic clay formation. The nanocomposite showed a balance to mechanical properties and anti‐microbial property.…”
Section: Introductionmentioning
confidence: 99%